PENGARUH PERSEPSI HARGA DAN KUALITAS TERHADAP NIAT BELI ULANG PRODUK PRIVATE LABEL BRAND (NON-FOOD CATEGORY) DI TOSERBA YOGYA & GRIYA KOTA BANDUNG - Riska Fitri Ratnafuri; Theresia Gunawan; Istiharini Istiharini (Journal of Management Small and Medium Enterprises (SMEs), 2022)
The purpose of this study is to analyze the effect of Perceived Price and Quality on Repurchase Intention for private label brand products (non-food category) at Yogya & Griya department stores, Bandung. This study uses 140 respondents who had purchased private label products (non-food category) twice in the last three months as sample consumers. The sampling used in this study is non-probability sampling technique. The method used is purposive sampling. This study uses questionnaire to collect data. Using the causal relationship method, it is employed the Validity Test, Reliability Test, the Classical Assumption Test, hypothesis test using the F test and t test, as well as analyze the Coefficient of Determination and Multiple Linear Regression. The result of this study shows that Perceived Price (X1) and Perceived Quality (X2) have a positive and significant effect on Repurchase Intention (Y), both partially and simultaneously, it can be said that Perceived Price and Quality are the determining factors in the Repurchase Intention of private label brand products (non-category), meaning that the higher the perceived price and quality, the more it will increase repurchase intention for private label brand products (non-food category). Keywords: Private Label Brand, Perceived Price, Perceived Quality, Repurchase Intention